The monster : illustrations by Christopher Myers - Myers, Walter Dean. (New York : Harper Collins Publishers, 1999)
While on trial as an accomplice to a murder, sixteen-year-old Steve Harmon records his experiences in prison and in the courtroom in the form of a film script as he tries to come to terms with the course his life has taken.
Keywords: Afro-Americans -- Fiction; Prisons -- Fiction; Self-perception -- Fiction; Trials (Murder) -- Fiction